Study Of The Status Of Diversity And Potential Of Fish In The Downstream Area Of The Brantas River (Mojokerto, Sidoarjo, Surabaya) As An Effort To Conserve Biological Biota In East Java - Kusuma Putri, Whidia Safira (Journal of Aquaculture Development and Environment, 2024)
The Brantas River is also a good aquatic habitat for the growth and development of fish. The types of fish in the river have the potential to be developed as a superior product of a region, as an effort to combine conservation efforts and economic development for local communities. However, the potential of river fisheries has not been maximized, therefore the need for a study of the potential of natural resources, especially fisheries that support environmental sustainability so that the utilization of the potential resources of the lower reaches of the Brantas River can improve the welfare of the surrounding community. Sampling was carried out at nine station points by purposive random sampling. Data analysis used is quantitatively based on the calculation of Shannon-Wienner diversity index (H'), dominance index (Di) and Pearson correlation test. The results obtained showed that the fish found in the lower reaches of the Brantas River amounted to 17 species classified into 13 families. The diversity index ranges from 1.32 - 2.22 with a medium index category. The dominance index is included in the low category, which means that there is no dominating fish species. Of the 17 fish species, 9 species have been cultivated, 7 species have the potential to be cultivated and 1 species is not cultivated.